If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -5y + 15 Reorder the terms: 0 = 15 + -5y Solving 0 = 15 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 0 + 5y = 15 + -5y + 5y Remove the zero: 5y = 15 + -5y + 5y Combine like terms: -5y + 5y = 0 5y = 15 + 0 5y = 15 Divide each side by '5'. y = 3 Simplifying y = 3
| -15=7v-14 | | 4(2y+1)=-2(y-12) | | 11=-2w-5 | | 6n+4-2=3n+6 | | 2z+13=19 | | -3u+18=0 | | -6(-7+-9f+7y)= | | -8-2(3-x)=0 | | 9x+6.52=5x+12 | | -20f+2(f-4f)=52 | | 16=-2t | | 6(a-5)+6=4(a-4) | | 4-m/5=11 | | 9y-4y=3 | | 3(x-1)-2(x^2+2x+3)-5(x+6)=0 | | 6x=2000 | | 4x=-2.2 | | (5*x+7)/(3x)-(2x-2)/(3x) | | -6(3x-1)=10 | | (2x-4)(3x+1)= | | 5(4x-3)+12=-2 | | 4w+3w=-11-17 | | 5x/3+2=7x+1/4 | | -9x-8=3x+8 | | -4w=5 | | x^4-x^2-2x-1=0 | | 2(3+x)=-12 | | 9x-8=6x+40 | | -(-4-2)= | | 1-5=3y+5y | | 4/5v-1/5v=3/5+3/5 | | 4s^2+12sp+9p^2=0 |